A Study on Change Management at Organisations - Pandey, Rajesh Kumar; Mishra, Anchal (International Journal of Engineering and Management Research, 2025)
Change management is a critical aspect of modern organizational strategy, aiming to facilitate smooth transitions and ensure sustained productivity and morale during periods of change. Change Management encompasses with the virtues of evaluating the current status, planning the transition of the momentum and leading to a coordinal future. Kurt Lewin through his Change Model Unfreeze – Change- Refreeze explains Change as a process & not an event. Change management is the process, tools and techniques to manage the people side of change to achieve the required business outcome. Change management incorporates the organizational tools that can be utilized to help individuals make successful personal transitions resulting in the adoption and realization of change. Change management is a structured approach to help organizations transition from their current state to a desired one. This study explores the intricacies of change management within organizations, examining the strategies employed to manage change, the challenges encountered, and the outcomes achieved. A descriptive study, conducted by the help of the secondary data aims to study the strategies adopted towards Change Management by the Organizations. The study further aims to understand the significance of Change Management at Organizations. The authors also contribute a Model towards Change Management. Through a comprehensive review of literature, this paper identifies key factors that contribute to successful change management, including leadership, communication, employee involvement, and adaptability. The findings provide valuable insights for organizations seeking to navigate change effectively and underscore the importance of a structured approach to managing transitions. The inferences are indicative in nature.